Posisi Perempuan Perspektif Ulama Klasik - Baehaqi Baehaqi (Universitas Islam Negeri Mataram, 2008)
One of the Islamic facets that attracts much attention and provokes debates among Muslim intellectuals is discourse of women’s position in classical Islamic doctrines: women’s position in private and public areas. Women are often seen as peripheral, second class citizen, marginal and victims of injustice constructed by society’s perceptions. Considering that, classic Muslim scholars are mainly blamed for women inequality because of their interpretation on Al-Qur’an and Hadis. Consequently, societies often view that women’s tasks are limited to domestic areas: kitchen, well, and bed. Therefore, Muslim thinkers should reinterpret Al-Qur’an and Hadis focusing on Islamic spirits that emphasize Islam as rahmat for all people, women and men, in all aspects of life.